(untitled) (American Journal of Pedagogical and Educational Research, 2025)
In the current context of developing artificial intelligence (AI) technologies, the role of worker skills in the labor market is undergoing significant transformation. This article explores ways to apply AI methods to assess current professional skills and forecast their future demand. Based on a literature review, recommendations are offered for stakeholders: employers, educational institutions, and public policy agencies.